2008
DOI: 10.1158/1535-7163.mct-07-2217
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of methylnaltrexone with 5-fluorouracil and bevacizumab on inhibition of vascular endothelial growth factor–induced angiogenesis

Abstract: Many patients with cancer receive combinations of drug treatments that include 5-fluorouracil (5-FU) and bevacizumab. Therapeutic doses of 5-FU are often associated with unwanted side effects, and bevacizumab is costly. Therefore, we explored potential agents that can reduce the therapeutic concentration of these drugs. Our data indicate that methylnaltrexone (MNTX), a peripheral antagonist of the M-opioid receptor, exerts a synergistic effect with 5-FU and bevacizumab on inhibition of vascular endothelial gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 49 publications
3
41
0
2
Order By: Relevance
“…Further, the model system predicted a synergy between chemotherapeutic agents and MNTX beyond the receptor level. A potentiation of MNTX on the anti-angiogenic effects of chemotherapeutic agents 5FU and bevacizumab has been reported in pulmonary endothelial cells 45 . Recent in vitro studies have determined that pseudomonas have mu opiate receptors that produce the lethality factors procyanin and PA-1L.…”
Section: Other Potential Uses Of Peripheral Opiate Antagonistsmentioning
confidence: 93%
See 1 more Smart Citation
“…Further, the model system predicted a synergy between chemotherapeutic agents and MNTX beyond the receptor level. A potentiation of MNTX on the anti-angiogenic effects of chemotherapeutic agents 5FU and bevacizumab has been reported in pulmonary endothelial cells 45 . Recent in vitro studies have determined that pseudomonas have mu opiate receptors that produce the lethality factors procyanin and PA-1L.…”
Section: Other Potential Uses Of Peripheral Opiate Antagonistsmentioning
confidence: 93%
“…Além disso, o modelo previu sinergia entre os agentes quimioterápicos e a MNTX além do nível do receptor. Relatou-se potencialização da MNTX nos efeitos antiangiogênicos dos quimioterápicos 5FU e bevacizumabe nas células endoteliais pulmonares 45 . Estudos in vitro recentes determinaram que pseudomonas têm receptores opióides mu que produzem os fatores de letalidade procianidina e PA-1L que são bloqueados pela MNTX, sugerindo efeito dos opióides na sépsis bacteriana que pode ser influenciada pelos antagonistas 46 .…”
Section: Outros Usos Potenciais Dos Antagonistas Periféricos Dos Opióunclassified
“…One hypothesis is that epidural anesthesia confers a protective effect directly or indirectly (through attenuation of a stress response), an alternative explanation is that endogenous and exogenous opioids during surgery may change endothelial permeability [Singleton et al, 2007]. Additionally a recent report showed synergistic effects of methylnaltrexone with 5-FU and bevacizumab on inhibition of VEGF-induced angiogenesis [Singleton et al, 2008] even in the absence of opioids.…”
Section: Treatment Of Opioid-induced Angiogenesismentioning
confidence: 99%
“…Μu-type opioid receptors are identified in several immunological cell subsets [25,26], and it has been demonstrated that opioids suppress T cell functioning and the production of several cytokines [23,27-29]. Activation of the μ-opioid receptor expressed on endothelial cells stimulates angiogenesis and a synergistic effect of morphine sulphate with VEGF has been demonstrated [21,30,31]. Methylnaltrexone could be of additive value to prevent this unwanted immunomodulatory and angiogenic activity of opioids [30].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the μ-opioid receptor expressed on endothelial cells stimulates angiogenesis and a synergistic effect of morphine sulphate with VEGF has been demonstrated [21,30,31]. Methylnaltrexone could be of additive value to prevent this unwanted immunomodulatory and angiogenic activity of opioids [30]. Therefore, we will study the effects of methylnaltrexone on immunomodulatory and angiogenic activity in patients during treatment with this agent.…”
Section: Introductionmentioning
confidence: 99%